Interactive Multimedia Based Long Jump Athletic Learning During the Covid-19 Pandemic at FIK UNIMED - Suharjo Suharjo; Imran Akhmad; Faridz Ravsamjani; Dicky Edwar Daulay (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Jump numbers are included in the classification of skill types that are acycliccombined. This means that there is a cyclic movement which is then continued with the acyclical movement so that it can take advantage of the part method (partmethod) and the whole (whole method). It provides an understanding of audio as something related to reception through sound and hearing. Visual is something related to the eye or vision, props, can be seen and witnessed. It can be said that audio visuals are "something related to reception through hearing and sight, sound and props, audible and witnessable". In this case, audio visual media is used to record the initial ability of students by analyzing movements using kinovea applications so that specific movement hasis are obtained. The use of audio visual media to evaluate the series of long jump movements can be one alternative in determining learning variations that are in accordance with the ability of students. The methods used in this study use development research. Research in this learning model uses quantitative approaches as well as using the Research & Development (R&D) development model of Borg and Gall. The product development procedure can be described as follows: a) Determination of ideas, b) Model making, c) Evaluation.The subject used in the athletics course of the Long Jump branch in FIK UNIMED students is qualitative data, because it is expressed by sentences and not numbers, while the quantitative data is obtained by converting qualitative data by giving a score to the data that has been collected.